Узагальнений показник якості енергії в електричних мережах і системах - Кузнєцов, В.Г.; Шполянський, О.Г.; Яремчук, Н.А. (Технічна електродинаміка, 2011)
The paper consider the questions of definition of the integrated power quality index taking into account simultaneous impact of voltage asymmetry on negative sequence and levels of voltage harmonics. The integrated power quality index allows coordinate electromagnetic compatibility levels under simultaneous presence of different distortions. The method of calculation of optimal harmonic factors for fixed set of the harmonics and voltage asymmetry on negative sequence is proposed. Uncertainty of measurement (definition) of the integrated power quality index based on uncertainty of measurement of its components is evaluated.